Detachment from Place : Beyond an Archaeology of Settlement Abandonment - Macrae, Scott, 1984-; Lamoureux-St-Hilaire, Maxime (Book collections on Project MUSE., 2020)
The first comparative and interdisciplinary volume on settlement abandonment, focusing on materiality, ideology, environment, and social construction of space. Case studies from around the world and time periods, shedding light on underexamined aspect of settlement abandonment wherein sedentary groups leave behind meaningful elements of their inhabited landscape.--description provided by publisher.